Predictors of difficult intubation in obstetric cohort of patients: an analysis of the prospective obstetric airway management registry (OBAMR) (substudy – R025/2018) - Burger, Adrian (Department of Anaesthesia and Perioperative Medicine, 2021)
Abstract Background: Hypoxaemia during tracheal intubation in obstetrics remains a lifethreatening complication. This study aimed to identify common clinical preinduction predictors of difficult intubation. Methods: A retrospective analysis was performed of data pertaining to tracheal intubation in patients requiring general anaesthesia for caesarean delivery, with a gestational age from 20 weeks, and until 7 days post-delivery, obtained from an obstetric airway management registry (ObAMR) at the University of Cape Town. Data was entered anonymously into a secure UCT REDCap database. Data categories were: patient and pregnancy characteristics, airway characteristics, details of management, and operator experience. The primary aim of the study was to identify anatomical and physiological risk factors for hypoxaemia. The primary outcome was defined as arterial desaturation to < 90% during obstetric airway management. For this purpose, multivariable binary logistic regression was performed. Hypoxaemia was thus used as a composite indicator of anatomical and physiological difficulty. Results: Data was collected for 1095 general anaesthetics in the ObAMR. Overall, 143/1091 of patients (13.1%, 95%CI 11.1 to 15.4%) experienced peripheral oxygen saturation below 90%. Univariate analysis showed that 91/142 (64.1%) of patients who desaturated were obese (body mass index [BMI]> 30 kg/m2 ), compared with 347/915 (37.9%) who were obese and did not experience desaturation (p< .001). A receiver operating curve (ROC) was constructed post hoc, which showed a cut-point for BMI of 29.76, and a sensitivity of 0.66, and specificity 0.62 for the prediction of hypoxaemia. Desaturation occurred in 17.0% of patients with hypertensive disorders of pregnancy, versus 11.0 % without (p=0.005). Increasing Mallampati class was associated with an increased incidence of hypoxaemia. The incidence of hypoxaemia was 25.8% for interns, compared with 8.0 % for consultant anaesthesiologists (p=0.005). In the multivariate analysis of factors associated with hypoxaemia, body mass index (p< 0.001), room air saturation prior to preoxygenation (p=0.008), and the presence of airway oedema (p=0.027), were independently associated with hypoxaemia. Conclusions: In this study, both anatomical and physiological predictors of hypoxaemia were identified. Using this concept, a predictive tool could be developed to aid in the identification of a difficult airway in obstetrics. Simple interventions such as face mask ventilation and the use of high flow nasal oxygenation, could be introduced to protect the parturient from the consequences of life-threatening hypoxaemia.